2017
DOI: 10.3390/atmos8100181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N Fertilizer Application on Soil N2O Emissions and CH4 Uptake: A Two-Year Study in an Apple Orchard in Eastern China

Abstract: Land use changes from cropland to orchards in Eastern China have raised serious concerns about the regional nitrogen (N) cycle and greenhouse gas balance. We measured soil nitrous oxide (N 2 O) emissions and methane (CH 4 ) uptake using manual static chambers in an apple orchard. The primary aims were to assess the effect of N fertilizer application on gas fluxes and quantify the site-specific N 2 O emission factor (EF d ). Field experiments were arranged in a randomized block design with three N input rates (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 42 publications
1
4
1
Order By: Relevance
“…In this study, average daily N 2 O emissions from wolfberry receiving 0-667 kg•ha −1 N ranged from 6.55-67.57 g N 2 O-N ha −1 •d −1 . Similarly, in eastern China, average daily N 2 O emissions from an apple orchard were 71.78 g N 2 O-N ha −1 •d −1 [20]. At a similar nitrogen rate, we report lower N 2 O emissions.…”
Section: Effects Of N Fertilizer Rate On Yield Ghg Emissions Gwp and ...supporting
confidence: 63%
See 1 more Smart Citation
“…In this study, average daily N 2 O emissions from wolfberry receiving 0-667 kg•ha −1 N ranged from 6.55-67.57 g N 2 O-N ha −1 •d −1 . Similarly, in eastern China, average daily N 2 O emissions from an apple orchard were 71.78 g N 2 O-N ha −1 •d −1 [20]. At a similar nitrogen rate, we report lower N 2 O emissions.…”
Section: Effects Of N Fertilizer Rate On Yield Ghg Emissions Gwp and ...supporting
confidence: 63%
“…Optimizing N fertilizer applications and using nitrification inhibitors may be effective strategies to improve N use rate and reduce the environmental costs of agricultural production [16,17]. It was revealed that N 2 O emission significantly decreased due to reduced N fertilizer rates [18][19][20][21]. The cumulative N 2 O emission decreased by 68.8% during the experiment when N fertilizer was decreased by 53.3% [22].…”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63]. High N 2 O emissions were observed in all treatments during the initial stage of fertilizer application, suggesting that addition of the N substrate increased microbial activity [60]. However, in general, the averaged N 2 O emissions were lower in the fertilizer treatments, because the study area was N limited.…”
Section: Nomentioning
confidence: 84%
“…Therefore, this helps explain the growth patterns of the emission peaks of N 2 O in the present study as the addition of nitrogen to pasture and agriculture (Figure 4B,C) increases. If soil moisture and available carbon are not the limiting factors, variations in nitrogen availability in the soil can also induce N 2 O emissions [12,28,55].…”
Section: Effect Of Nitrogen Addition To the Soil On N 2 O Emissionmentioning
confidence: 99%